Distributed synchronization of autonomous underwater vehicles with memorized protocol. (24th April 2019) - Ma, Chao; Wu, Wei
This article investigates the distributed synchronization problem of autonomous underwater vehicles by developing a novel synchronization protocol with memorized controller. More precisely, the memory information for information exchanges of autonomous underwater vehicles is utilized such that the synchronization performance can be improved. By employing the Lyapunov–Krasovskii functional method with model transformation, sufficient criteria are established for guaranteeing the synchronization, and the corresponding distributed synchronization controllers are designed based on matrix techniques. Finally, the effectiveness and benefits of our theoretical method are supported by an illustrative example with simulation results.